Chronicle - Archives of Acoustics, Editorial Board (Archives of Acoustics, 1997)
1. The new president of the Polish Acoustical Society.2. The new Authorities of Polish Acoustical Society elected on 15.10.1996 by the General Assembly of Delegates.3. 101st AES Convention, Los Angeles, 8-11 November 19964. The Acoustical Conferences organized in Poland 1n 1997.5. New doctoral thesis in acoustics - Characteristics of back cattering ultrasonic signals from the floor of Southern Baltic, Jarosław Tęgowski, Institute of Oceanology, Polish Academy of Sciences, Sopot, 3. Obituary - Ph.D. Janusz Zalewski